'Other Animal Ethics' and the Demand for Difference. (1st May 2002) - Aaltola, E.
Traditionally animal ethics has criticised the anthropocentric worldview according to which humans differ categorically from the rest of the nature in some morally relevant way. It has claimed that even though there are differences, there are also crucial similarities between humans and animals that make it impossible to draw a categorical distinction between humans who are morally valuable and animals which are not. This argument, according to which animals and humans share common characteristics that lead to moral value, is at the heart of animal ethics. Lately the emphasis on similarity has been under attack. It has been claimed that the search for similarity is itself part of anthropocentric morality, since only those like us are valuable. It also has been claimed that true respect for animals comes from recognising their difference and 'otherness', not from seeing similarities. This paper analyses the new 'other animal ethics' by critically examining its basis and consequences. The conclusion is that despite the fact that other animal ethics is right in demanding respect also for difference, it remains both vague and contradictory in its theoretical basis, and leads to undesirable consequences from the perspective of animal welfare.